Social Context, Gender Identity and Eating Disorders in Western and Eastern Europe: Preliminary Results of a Comparative Study - Catina, Ana; Boyadjieva, Svetlana; Bergner, Michaela (European eating disorders review, 1996)
The present paper reports preliminary results of a pilot study carried out on two samples of females living in two different European countries. The onset of eating disorders is considered to result from females' difficulties in developing a gender‐specific identity in a specific social context that provides and supports certain ideals, interpersonal relationships, and attitudes toward them. Thirty‐five German females and 20 Bulgarians have been questioned about the way they perceive themselves, the social ideal, the attractivity in women, the problem of individuation and separation, autonomy and social relationship in general. The results indicate that certain social models are more likely to induce identity conflicts in the German sample than in the Bulgarian one.